2017
DOI: 10.4102/ojvr.v84i1.1240
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and effect of gastrointestinal nematodes on dairy goats in Argentina

Abstract: The aim of this work was to study the epidemiology and harmful effects of gastrointestinal nematodes (GINs) on dairy goats maintained in an intensive system. Two groups of goats were studied: untreated group (UG) (subdivided into UGjun goats that kidded in June, and UGjul goats that kidded in July) and treated group (TG) (with no subgroups, treated with monepantel: 3.75 mg/kg, orally, monthly). Eggs per gram (epg) in faeces were counted, faecal culture was performed to differentiate nematode genera and milk pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
2
6
0
8
Order By: Relevance
“…According to Suarez et al (2009), anthelmintic treatment positively affects the length of the milking period with regard to the length of the milking period of untreated dairy sheep. The same way, Suarez et al (2017) revealed, in goats instead, a significant negative effect of the GIN infections on the milking period length of the goats after kidding (262.3±9.8 days and 223.3±10.8 days respectively for treated and untreated goats). These different results could explain the positive correlation between the GINs infections treatment and the persistence increase in milk yield in dairy goats, ranging from 7.4 to 18.5% with respect to control values observed by Rinaldi et al (2007).…”
Section: Effects Of H Contortus Infections On Small Ruminants' Productionsupporting
confidence: 52%
See 1 more Smart Citation
“…According to Suarez et al (2009), anthelmintic treatment positively affects the length of the milking period with regard to the length of the milking period of untreated dairy sheep. The same way, Suarez et al (2017) revealed, in goats instead, a significant negative effect of the GIN infections on the milking period length of the goats after kidding (262.3±9.8 days and 223.3±10.8 days respectively for treated and untreated goats). These different results could explain the positive correlation between the GINs infections treatment and the persistence increase in milk yield in dairy goats, ranging from 7.4 to 18.5% with respect to control values observed by Rinaldi et al (2007).…”
Section: Effects Of H Contortus Infections On Small Ruminants' Productionsupporting
confidence: 52%
“…Indeed, in Italy, a study involving untreated naturally infected and anthelminthic-treated animals has revealed significantly effect of GINs infections on milk production, with the highest milk yield recorded in the treated goats (Rinaldi et al, 2007). More recently, in Argentina, Suarez et al (2017) reported a significant difference in the mean total milk production between treated (399.5 L ± 34.0 L) and untreated goats (281.6 L ± 37.5 L), amounting to 41.8% increase in total milk yield. The same study also revealed a post-partum peak in egg count and a negative effect of gastrointestinal nematodes (GINs) on milk yield, even with moderate infections.…”
Section: Effects Of H Contortus Infections On Small Ruminants' Productionmentioning
confidence: 99%
“…Although H contortus infection generally occurs together with other gastrointestinal nematodes, it consistently dominates the infection among livestock in tropical or subtropical countries . For example, milk production in Saanen goats naturally infected with H contortus and Trichostrongylus colubriformis and subsequently treated with anthelmintic is significantly higher (399.5 L ± 34.0 L; P < .05) when compared to untreated goats (281.6 L ± 37.5 L) …”
Section: Introductionmentioning
confidence: 98%
“…A partir de estos resultados se podría inferir que la mayor infestación se registraría al inicio del otoño cuando el desarrollo de los NGI se vería favorecido por las lluvias estivales. A pesar de que los muestreos de heces no mostraron los niveles de infestación descritos en las explotaciones comerciales de los valles templados de altura de Salta y Jujuy (Suarez et al, 2017c), las principales especies presentes coincidieron con las de esa región. En otros muestreos en otras regiones áridas también se observó la presencia en bajo número de los géneros Trichostrongylus spp.…”
Section: Presencia De Parásitos Y Enfermedades Parasitariasunclassified